Área de vida e biologia reprodutiva da maria-da-restinga (Phylloscartes kronei) (Aves, Tyrannidae) - Gussoni, Carlos Otávio Araújo [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Little is known about natural history of the globally threatened Restinga Tyrannulet (Phylloscartes kronei). This work aimed to describe its home range and territory, and collect new information about its breeding biology. We captured and banded with coloured bands 28 individuals at Reserva Bicudinho-do-brejo (Guaratuba, PR) and four at Parque Natural Municipal da Lagoa do Parado. Field work was conducted monthly from January 2012 to December 2013, comprising 211 days of field observations. The individuals home range size was 1.76 ± 0.93 ha and the home range size of pairs was 2.52 ± 1.91 ha. There weren´t differences between the home range size of males and females and the home range size of individuals and pairs throughout the study. In 2012 we found different home range size of the individuals inside and outside the breeding season, whereas this was not observed in 2013. The home range size of pairs did not vary inside and outside the breeding season. We found extensive overlapping on home range. The territory size was recorded for two adjacent pairs: 0.68 and 0.46 ha. We surveyed individuals in a 21 ha area and obtained a density of 1.04 pairs/ha. The breeding season started in September and the last signs of reproduction were recorded in January. Nests were built between 0.72 and 3 m above the ground. All nests were closed ovoids internally built with dry leaves and externally lined with green mosses. The materials were glued with spider web and the oological chamber lined with soft seeds. The predation rate was 60% and the Mayfield success for the incubation period was 42.42%. One pair whose nest was predated built another nest 52 meters away. The second nest was predated and the pair built another one 93 meters away. Other pair whose nest was predated built a new nest 51 meters away. It took about 19 days to build the nests and they were all made by females. The clutch size varies from 2 to 3 white eggs (15.9 – 16.8 mm x...

A maria-da-restinga (Phylloscartes kronei) é um tiranídeo globalmente ameaçada de extinção, cuja história natural é pouco conhecida. Este trabalho teve como objetivo descrever sua área de vida, território e biologia reprodutiva. Foram capturados e marcados com anilhas coloridas 32 indivíduos no município de Guaratuba, PR. De janeiro de 2012 a dezembro de 2013 foram realizados 211 dias de observações. A área de vida dos indivíduos foi de 1,76 ± 0,93 ha e a dos casais 2,52 ± 1,91 ha, havendo extensa sobreposição nestas áreas. Não houve diferença nas áreas de vida de machos e fêmeas e entre a área de vida dos indivíduos e casais em 2012 e 2013. Houve diferença nas áreas de vida dos indivíduos dentro e fora do período reprodutivo apenas em 2012. O tamanho da área de vida dos casais não variou dentro e fora do período reprodutivo. O tamanho de território foi determinado para dois casais: 0,68 e 0,46 ha. A densidade populacional em 21 ha foi de 1,04 casais/ha. Os primeiros sinais de reprodução ocorreram em setembro e os últimos em janeiro. Os ninhos foram construídos entre 0,72 e 3 m acima do solo, sendo fechados e ovalados. Foram construídos internamente de folhas secas de gramíneas e forrados externamente por musgos verdes, sendo os materiais colados com teia-de-aranha e a câmara oológica forrada com sementes plumosas. A taxa de predação dos ninhos foi de 60% e o Sucesso de Mayfield para o período de incubação foi de 42,42%. Um dos casais que teve o ninho predado construiu outro a 52 m de distância do anterior, que foi igualmente predado, sendo o terceiro construído a 93 m de distância do último. Outro casal, que teve seu ninho predado, construiu outro a 51 m de distância. A construção durou aproximadamente 19 dias e foi tarefa exclusiva das fêmeas. O tamanho da postura foi de dois a três ovos brancos (15,9–16,8 mm x 12,7–13,1 mm). A incubação foi tarefa exclusiva das fêmeas e durou...
Keywords: Birds; Ave; Reprodução animal; Ornitologia; Historia natural; Morfometria; Predação (Biologia)